Organização do trabalho docente na educação a distância : implicações da polidocência no contexto da Universidade Aberta do Brasil (UAB) - Veloso, Braian Garrito (Universidade Federal de São Carlos, 2018)
The Distance Education has undergone significant changes that concerns the way in which the teaching work is organized. In the modality, not just one, but multiple professionals should work in consonance to guarantee the teaching-learning processes. In addition, in the Brazilian experience, the Distance Education has been developed, in public institutions, by policies with an emergency character such as the Universidade Aberta do Brasil System (UAB). In addition to the inherent complexities of the teaching work in Distance Education, it is added, therefore, related aspects in the precariousness of work. Thus, this research has the main objective of analyze the consequences from the teaching work organization in the Distance Education in light of the concept of polidocência. In order to meet the main objective, our analysis is based on five specific objectives: to perform a bibliometric study on the scientific production of the area; to characterize the Universidade Aberta do Brasil system and the configuration of the teaching adopted in its courses, analyzing the implications in the institutionalization of the Distance Education; to discriminate the division of teaching work and its implications for teaching in the Distance Education; to investigate the labor relations between teachers in the Distance Education; to explore the teacher knowledge used in Distance Education and its implications in the relations of power and knowledge in the context of polidocência. About the methodology, we used methodological triangulation, considering that we simultaneously used qualitative and quantitative methods. The methodological procedures, in turn, occurred as follows: bibliometric analysis using the thesis basis elaborated by the Grupo Horizonte; documentary analysis from the pedagogical projects of courses offered under the UAB System; application of virtual questionnaires to teachers-authors, teachers-applicators and virtual and face-to-face tutors who work or have already worked in the UAB System; semi structured interviews with these same teachers. Through this research, we observed that the researches about Distance Education and especially about teaching work in the modality, still represent a very small part of the scientific production related to Education in Brazil. We also verified that the UAB System has standardized the configuration of teaching work in the Distance Education. Our study also reveals that teaching in the modality is divided and fragmented, so that each professional is responsible for a specific set of activities and functions. In addition, the Distance Education has characteristics related to productive restructuring, such as flexibilization and teleworking, which, among other aspects, promote perversities for the teachers. In the research we also identified that the constitution of teaching knowledge is complex. Thus, the knowledge base for the teaching of each professional comes from multifaceted sources and includes knowledge of digital technologies. Our study also suggests that the relations of knowing relate to those of power in the context of polidocência.
Organization of teaching work in distance education : implications of polidocência in the context of the Universidade Aberta do Brasil (UAB) system
Keywords: Polidocência; Sistema Universidade Aberta do Brasil; Educação a distância; Trabalho docente; Distance education; Teaching work; Universidade Aberta do Brasil System; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO